2019
DOI: 10.2174/1874467212666181218113930
|View full text |Cite
|
Sign up to set email alerts
|

MiR-597 Targeting 14-3-3σ Enhances Cellular Invasion and EMT in Nasopharyngeal Carcinoma Cells

Abstract: Background: Alterations in microRNAs (miRNAs) are related to the occurrence of nasopharyngeal carcinoma (NPC) and play an important role in the molecular mechanism of NPC. Our previous studies show low expression of 14-3-3σ (SFN) is related to the metastasis and differentiation of NPC, but the underlying molecular mechanisms remain unclear. Methods: Through bioinformatics analysis, we find miR-597 is the preferred target miRNA of 14-3-3σ. The expression level of 14-3-3σ in NPC cell lines was detected by West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A large number of studies have found that the occurrence of EMT biological behavior plays an important role in the metastasis of malignant tumors [16][17][18]. In gastric cancer, many signaling pathways were involved in the regulation of EMT, and signaling pathways such as PI3K/AKT [19], MEK/ERK [20], and WNT/β-Catenin [21], especially TGF-β/ SMAD [22,23] play important roles.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have found that the occurrence of EMT biological behavior plays an important role in the metastasis of malignant tumors [16][17][18]. In gastric cancer, many signaling pathways were involved in the regulation of EMT, and signaling pathways such as PI3K/AKT [19], MEK/ERK [20], and WNT/β-Catenin [21], especially TGF-β/ SMAD [22,23] play important roles.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-597-3p is located on the 8p23.1 chromosome ( 21 ). Xie et al ( 22 ) reported that miR-597 targeting 14-3-3σ enhances cellular invasion and the epithelial-mesenchymal transition in nasopharyngeal carcinoma cells, whilst Zhang et al ( 23 ) revealed that a low expression of miR-597 is correlated with tumor stage and a poor outcome in breast cancer. FOSL2 is a member of the AP-1 transcription factor family ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-9-3p suppressed the EMT process via downregulating FN1, ITGB1, ITGAV expression to reduce the proliferation and metastases of NPC; 26 miR-BART8 -3p involved in EMT of NPC cells through directly targeting RNF38 to activate NF-κB and Erk1/2 signaling axis, thereby promoting NPC progression and metastasis; 27 miR-597 promoted cellular EMT to enhance the migration and invasion of NPC cells by targeting 14-3-3σ (SFN). 28 In this study, we found that the ectopic expression of miR-379-5p obviously suppressed the EMT program, thereby inhibiting the migration and invasion of NPC cells, whereas the inhibition of miR-379-5p exerted the opposite effect. These data implicate that miR-379-5p is an important regulator of EMT in NPC.…”
Section: Discussionmentioning
confidence: 62%